2022
DOI: 10.4103/ijo.ijo_802_22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of femtosecond laser–assisted cataract surgery versus conventional phacoemulsification: A retrospective study in a tertiary eye care center in South India

Abstract: Purpose: To compare the clinical outcomes of femtosecond laser–assisted cataract surgery (FLACS) versus conventional phacoemulsification (CP) in terms of refractive outcomes, cumulative dissipated energy, and intraoperative complications. Methods: In this retrospective study performed in a tertiary care ophthalmic hospital, we reviewed 2124 eyes that underwent FLACS or CP. Uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), cumulative dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…FLACS has also been reported to reduce optical aberrations and improve optical quality and patient satisfaction 32–34 . Several studies have reported that FLACS showed better visual outcomes than conventional cataract surgery, particularly in cases with implantation of an extended-depth-of-focus IOL 16,34,35 . However, other studies failed to demonstrate any significant difference in visual and refractive outcomes between FLACS and conventional cataract surgery 5,36–39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FLACS has also been reported to reduce optical aberrations and improve optical quality and patient satisfaction 32–34 . Several studies have reported that FLACS showed better visual outcomes than conventional cataract surgery, particularly in cases with implantation of an extended-depth-of-focus IOL 16,34,35 . However, other studies failed to demonstrate any significant difference in visual and refractive outcomes between FLACS and conventional cataract surgery 5,36–39 .…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Several studies have reported that FLACS showed better visual outcomes than conventional cataract surgery, particularly in cases with implantation of an extended-depth-of-focus IOL. 16,34,35 However, other studies failed to demonstrate any significant difference in visual and refractive outcomes between FLACS and conventional cataract surgery. 5,[36][37][38][39] Metaanalysis studies revealed that FLACS did not show significant difference for visual and refractive outcomes, whereas it was associated with a higher rate of complications, such as incomplete capsulotomy, anterior capsular tear, and posterior capsular rupture.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of SING IMT™, if compared with the first generations IMT™, is the new device design and technique, allowing small corneal wound, the preloaded device, as well as the shorter surgery time. Further advantages expected from the use of FLACS could not be evaluated because we did not use assisted nuclear fragmentation and it is clearly known that the reduction of postoperative ECD loss is mainly due to a reduced cumulative dissipated energy during laser-assisted phacoemulsification [ 19 ]. However, the possibility of setting pre-operatively some anatomical parameters (e.g., the diameter of the capsulorhexis) increases surgical repeatability, predictability, shape accuration and strength of capsulorhexis, as well as reducing the risk of complications, compared to the manual procedure [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In white, complete, or intumescent cataracts, studies have found that adjustment of femtosecond laser capsulotomy distance by reducing pre-anterior capsule and increasing postanterior distance may decrease the incidence of incomplete capsulotomies. [16][17][18] The femtosecond laser allows nucleus fragmentation can be performed through various cutting patterns including cubes, sections, or grooves depending on surgeon preference and density of the cataract. As complications in cataract surgery including posterior capsule tear can frequently arise during nuclear disassembly, nuclear pre-cutting and nuclear softening with the femtosecond laser reduces the ultrasound energy required.…”
Section: Cataract Surgerymentioning
confidence: 99%